Analyzing Errors in Academic Essays Written by English Department Students - Kurniati, Ruri Fadhilah (LPPM Universitas Advent Indonesia, 2019)
English Department students are expected to be able to write an academic essay as they learn the theories of writing an academic essay in Writing courses. Yet, their academic essays still contain structure errors. This study aims to analyze the structure errors in the fields of unity and coherence. The methods of this study are first identifying the structure errors on the data and second classifying the errors on whether the error is about the unity or coherence. The finding shows a significant number of errors on unity and coherence in most paragraphs of the essays.